MATERNAL SELF-EFFICACY FOR PREMATURE NEWBORN CARE AND BREASTFEEDING MAINTENANCE - Squizato, Leticia; Silva, Aline Dahmer da; Martinelle, Eduarda; Machineski, Gicele Galvan; Toso, Beatriz Rosana Goncalves de Oliveira; Viera, Claudia Silveira (Cogitare Enfermagem, 2023)
Objective: to assess maternal self-efficacy for the care of premature newborns in the neonatal intensive care unit and after hospital discharge and relate it to the duration of breastfeeding at home. Method: longitudinal study that used self-efficacy assessment scales of 38 mothers of premature newborns in the period from November 2020 to January 2022 in the city of Cascavel - PR - Brazil. Data analyzed by descriptive and inferential statistics. Results: Maternal self-efficacy during hospitalization turned out to be high, remaining so in the assessment after discharge. Self-efficacy for breastfeeding had no statistically significant differences during hospitalization (p=0.335) and after discharge (p=0.640). However, mothers with high self-efficacy in hospitalization and at home maintained exclusive breastfeeding longer. Conclusion: Identifying maternal self-efficacy should be a routine in nursing clinical practice during hospitalization and after discharge, to enhance the maintenance of exclusive breastfeeding.